Chemical composition is of the essential oil from (Desmos cochinchinensis var. fulvescens Ban) from Ha Tinh province - Dai, Do Ngoc; Thang, Tran Dinh; Dung, Nguyen Xuan (Academia Journal of Biology, 2014)
The leaf oil of Desmos cochinchinensis var. fulvescens Ban collected from Ha Tinh province, Vietnam, in October 2006 was isolated by steam distillation to give oil yield 0.15% and analyzed by Capillary GC and GC/MS. Fifty three components have been identified accounting more than 89.7% of the oil respectively. The major constituents of this oil appeared to be β-elemen (16.1%), d-cadinen (13.8%) and β-caryophyllen (13.7%). Less predominant constituents germaren B (7.7%), germacren A (5.7%), epizonaren (3.9%), elemol (3.6%), α-humulen (2.7%), a-pinen (2.3%), β-selinen (2.3%), g-terpinen (1.8%), d-elemen (1.7%), β-cubenen (1.5%), eudesma-4 (15), 11-dien-9-on (1.3%), α-selinen (1.3%) and g-elemen (1.1%).